Making Sense of Network Dynamics through Network Picturing - Tiina Valjakka; Valtteri Kaartemo; Katri Valkokari (Springer, 2022)
The future structure and paths of development of dynamic business networks are fundamentally unknowable. The managerial challenge is to influence the development within a business network crossing organizational boundaries. Practical tools are needed to map out how actors’ network strategies actually come into being while organizations continuously interact with each other. The described cases explore sense-making processes between the involved network actors and utilize network pictures as a boundary-spanning tool for strategic management. First, network picturing was utilized by a multinational company to identify the needs of actors in its network and to develop their value propositions under various network scenarios. Second, an SME’s (Small and medium-sized enterprise)most important connections were identified with network picturing to enable the company to drive changes in the network. The broader network perspectives depicted were the end users’ network pictures from different customer segments. In both cases, network picturing resulted in the identification of new relevant network actors and the requirements for building connections to them.
Practices for Network Management: In Search of Collaborative Advantage